Self assessment : an opportunity to reduce tax / Wan Faizah Wan Abdullah - Wan Abdullah, Wan Faizah (Universiti Teknologi MARA Kedah, Sungai Petani, 2002)
This paper explains the new Inland Revenue Board's Self Assessment System and its implication for the taxpayers. This paper also discusses tax evasion and tax avoidance and their legal consequences. Besides, some suggestions on how to avoid tax legally has been given in general. The antitax avoidance provision, which is designed to counter tax avoidance is also discussed in this paper.